Medical educators' experiences on medically unexplained symptoms and intercultural communication - Sallay Viola; Martos Tamás; Lucza Lilla; Weiland Anne; Stegers‐Jager Karen M.; Csabai Márta (2022)
Background Medically unexplained symptoms (MUS) are highly prevalent and remain challenging in healthcare and medical education, along with the increase in the importance of intercultural issues regarding MUS. However, less is known about the challenges of professionally addressing patients with MUS in the interprofessional and intercultural contexts. Thus, the present study aims to provide the first exploration of the experiences of medical specialists regarding treating MUS in intercultural contexts and inputs for training development on the intercultural aspects of MUS. Methods Three focus groups (total n = 13) consisting of medical specialists from a Hungarian university who were teaching at the medical faculty in intercultural settings and also worked for the university health services were interviewed. The topics covered the participants' personal experiences on addressing MUS and the challenges of intercultural communication and the intercultural educational context. Thematic analysis was used to yield a qualitative account of the interviews as guided by the research questions. Results Representing the different aspects of medical specialists, the study identified three main themes in the experiences of medical specialists, namely, 1) the need to adapt to the personal world of patients and search for common frames to understand MUS, 2) the need to discover methods for adapting to cultural differences and 3) the need to enhance the interprofessional coordination of knowledge and practices. Conclusions The results are in line with the distinct conclusions of previous studies. Moreover, an integrated educational program on the intercultural aspects of MUS may address the main themes separately and, subsequently, support their integration. Therefore, the study discusses the manner in which an integrated educational program on the intercultural aspects of MUS may address the needs recognized in these aspects.
Keywords: Pszichológia; Oktatástudomány